ISOLASI DAN SELEKSI JAMUR PENDEGRADASI SENYAWA BENSONITRIL - YS Subowo; Bambang Sunarko; Indrawati Gandjar (BERITA BIOLOGI, 2003)
A study on Isolation and selection of benzonitrile degrading fungi were conducted. The aim of this study was to obtain fungi that high potentially on degrading nitrile compounds. Microbial sources were derivat from industrial wastes. fungi-infecting plantand fungi grown on decayed wood. Eighteen isolates were isolated from those samples. Five isolates were capable to grow on benzonitrile. Isolate-AVI which was identified as Fusarium oxysporum was capable of degrading 0.15% (v/v) benzonitrile.